Генерації вчених-істориків та «Великий терор»: від інтелектуальної покори до репресій (на прикладі одеської корпорації гуманітаріїв) - Левченко, В. (Краєзнавство, 2017)
У статті здійснюється спроба дослідження відносини комуністичного адміністративно-ідеологічного
апарату та наукової інтелігенції в умовах «Великого терору» 1937–1938 рр. відповідно щодо запропонованих автором генерацій одеських вчених-істориків. Виявлено основні форми і методи репресивної політики
щодо вчених. Розглянуто найважливіші архівно-слідчі справи проти науковців. Подаються нові досі невідомі
історичні факти та документи, повернуто до історичного вжитку забуті імена діячів культури. The article attempts to study the relations of the communist administrative-ideological apparatus and the
scientific intelligentsia in the conditions of the «Great terror» of 1937–1938 years. Respectively, the generation
of Odessa scientists-historians proposed by the author. The main forms and methods of repressive policy regarding
scientists. The most important archival and investigative cases against scientists. New facts and documents
that have been hitherto unknown, new names of cultural figures have been returned to the historical
reference. In 1937–1938 years Indoctrination historians did not stop, and received new touches that differed
from previous new motives, methods, intensity, etc. effects. Negative developments became what historians have
gradually drawn into the yoke of the official ideology and the party-state control. This situation misled scientists
and historians fear the current government, disagreement which led to the restriction of academic freedom,
which is manifested in total regulation and standardization of various professional and harassment (of dismissal
to the far-fetched criminal liability). This has led to further serious negative consequences for the historical
development of education and science in particular, in Odessa in the USSR as a whole, significantly reducing
its quality and performance establishments stalled, out of which there has been only after almost sixty years. В статье осуществляется попытка исследования отношений коммунистического административно-идеологического аппарата и научной интеллигенции в условиях «Большого террора» 1937–1938
гг. соответственно предложенным автором генерациям одесских ученых-историков. Выявлены основные формы и методы репрессивной политики в отношении ученых. Рассмотрены важнейшие архивно-следственные дела против ученых. Подаются новые доселе неизвестные факты и документы, возвращено в историческое упоминание забытые имена деятелей культуры.